2018
DOI: 10.1103/physrevb.98.155127
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zn doping on the antiferromagnetism in kagomeCu4xZnx(OH)6FBr

Abstract: Barlowite Cu4(OH)6FBr shows three-dimensional (3D) long-range antiferromagnetism, which is fully suppressed in Cu3Zn(OH)6FBr with a kagome quantum spin liquid ground state. Here we report systematic studies on the evolution of magnetism in the Cu4−xZnx(OH)6FBr system as a function of x to bridge the two limits of Cu4(OH)6FBr (x=0) and Cu3Zn(OH)6FBr (x=1). Neutrondiffraction measurements reveal a hexagonal-to-orthorhombic structural change with decreasing temperature in the x = 0 sample. While confirming the 3D… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(64 citation statements)
references
References 53 publications
9
55
0
Order By: Relevance
“…Here, strong residue spin fluctuations, in the form of intralayer spin singlet formation due to the structure distortion (both displacements of Cu2 and deformation of kagome planes), are reported below magnetic transition at 15 K. 35 For systems with unique and homogeneous relaxation rate, the value of the stretch exponent will be β = 1. In contrast, a reduced value of β (< 1) indicates a wide distribution of relaxation rates.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Here, strong residue spin fluctuations, in the form of intralayer spin singlet formation due to the structure distortion (both displacements of Cu2 and deformation of kagome planes), are reported below magnetic transition at 15 K. 35 For systems with unique and homogeneous relaxation rate, the value of the stretch exponent will be β = 1. In contrast, a reduced value of β (< 1) indicates a wide distribution of relaxation rates.…”
Section: Resultsmentioning
confidence: 85%
“…The local structure of barlowite may not be well described by the average hexagonal model, a conclusion that goes in line with the very recent diffraction studies reporting orthorhombic symmetry of the crystal structure. 34,35 Insights into the spin dynamics can be obtained by measuring the spin lattice relaxation rates (1/T 1 ) as a function of temperature. 79 Br and 81 Br nuclear spin-lattice relaxation time T 1 were measured using a conventional inversion recovery pulse sequence at 84.44 MHz (at 7.4 T for 81 Br and 8.2 T for 79 Br).…”
Section: Resultsmentioning
confidence: 99%
“…α-Cu 3 Mg(OH) 6 Br 2 was synthesized by the hydrothermal method as described previously 26,39 . The mixture of 1.5-mmol Cu 2 (OH) 2 CO 3 and 6-mmol MgBr 2 •6H 2 O was sealed in a 50-ml reaction vessel with 25-ml water, which was slowly heated to 200 • C and kept for 12 hours.…”
Section: Methodsmentioning
confidence: 99%
“…The idea for the compound of Cu 3 Mg(OH) 6 Br 2 comes from the substitution of interlayer Cu 2+ in the barlowite Cu 4 (OH) 6 FBr, which has perfect Cu 2+ kagome layers with Cu 2+ ions between them and is antiferromagnetically ordered at about 15 K [36][37][38][39][40] . It has been theoretically suggested that Zn 2+ or Mg 2+ ions can replace the interlayer Cu 2+ in barlowite and thus dilute the AF order to give rise to a QSL state as in herbertsmithite 41,42 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation